Methods of NKGB in research crimes against humanity in 7th decade of XX century - Maripuu, Meelis (Genocidas ir rezistencija, 2006)
In the early 1960s, a new wave of trials was launched in the USSR against people who, based on compromising material, had been found to have collaborated with the German occupation authorities. Speaking in modern terms, they were charged with what is nowadays described as war crimes and crimes against humanity. The findings of this study demonstrate that the accusations were based on real facts. However, the methods used in the investigative process and when presenting an indictment led to the conclusion that this was not an objective investigation of the guilt of the suspects or delivery of a fair verdict. The interrogation and judicial bodies used such processes primarily for political, intelligence or other purposes.
Keywords: Estonia; crimes against humanity; KGB; repressions; Holocaust